Infrastructure, Environment, and Regional Development in South-Eastern Mongolia - World Bank (Washington, DC, 2017)
This report was written in 2008 in the wake of a World Bank mission to Mongolia in 2007. The team identified that the South Gobi region is poised for a major boom in economic activity, with a foundation based on planned development of mines of world class significance. The Mongolian Parliament is considering an greement with Ivanhoe Mines for the development of a copper and gold mine at Oyu Tolgoi, and a shareholder agreement that relates to proposed development of a coal mine at Tavan Tolgoi. Other proposed mines in the relatively near future include copper and molybdenum at Tsagaan Suvraga (TS) and export coal at Nariin Sukhait. It is likely that infrastructure development in the region will spur the development of additional mines and associated industries. The following discussion sets out the major infrastructure, environment, and regional development issued identified by the October mission of the World Bank.